Protocolized Treatment Is Associated With Decreased Organ Dysfunction in Pediatric Severe Sepsis*. Issue 9 (September 2016) - Balamuth, Fran; Weiss, Scott L.; Fitzgerald, Julie C.; Hayes, Katie; Centkowski, Sierra; Chilutti, Marianne; Grundmeier, Robert W.; Lavelle, Jane; Alpern, Elizabeth R.
Abstract : Objectives: To determine whether treatment with a protocolized sepsis guideline in the emergency department was associated with a lower burden of organ dysfunction by hospital day 2 compared to nonprotocolized usual care in pediatric patients with severe sepsis. Design: Retrospective cohort study. Setting: Tertiary care children's hospital from January 1, 2012, to March 31, 2014. Subjects: Patients older than 56 days old and younger than 18 years old with international consensus defined severe sepsis and who required PICU admission within 24 hours of emergency department arrival were included. Measurements and Main Results: The exposure was the use of a protocolized emergency department sepsis guideline. The primary outcome was complete resolution of organ dysfunction by hospital day 2. One hundred eighty nine subjects were identified during the study period. Of these, 121 (64%) were treated with the protocolized emergency department guideline and 68 were not. There were no significant differences between the groups in age, sex, race, number of comorbid conditions, emergency department triage level, or organ dysfunction on arrival to the emergency department. Patients treated with protocolized emergency department care were more likely to be free of organ dysfunction on hospital day 2 after controlling for sex, comorbid condition, indwelling central venous catheter, Pediatric Index of Mortality-2 score, and timing of antibiotics and IV fluids (adjusted odds ratio, 4.2; 95% CI, 1.7–10.4). Conclusions: Use of a protocolized emergency department sepsis guideline was independently associated with resolution of organ dysfunction by hospital day 2 compared to nonprotocolized usual care. These data indicate that morbidity outcomes in children can be improved with the use of protocolized care. Abstract : Supplemental Digital Content is available in the text.